"This has definitely opened the doors": Provider perceptions of patient experiences with telemedicine for contraception in Illinois. Issue 3 (7th September 2022) - Song, Bonnie; Boulware, Angel; Wong, Zarina Jaffer; Huang, Iris; Whitaker, Amy K.; Hasselbacher, Lee; Stulberg, Debra
Abstract: Context: The COVID‐19 pandemic increased the provision of contraception through telemedicine. This qualitative study describes provider perceptions of how telemedicine provision of contraception has impacted patient care. Methods: We interviewed 40 obstetrics‐gynecology and family medicine physicians, midwives, nurse practitioners, and support staff providing contraception via telemedicine in practices across Illinois, including Planned Parenthood of Illinois (PPIL) health centers. We analyzed interview content to identify themes around the perceived impact of telemedicine implementation on contraception access, contraceptive counseling, patient privacy, and provision of long‐acting reversible contraception (LARC). Results: Participants perceived that telemedicine implementation improved care by increasing contraception access, increasing focus on counseling while reducing bias, and allowing easier method switching. Participants thought disparities in telemedicine usage and limitations to the technological interface presented barriers to patient care. Participants' perceptions of how telemedicine implementation impacts patient privacy and LARC provision were mixed. Some participants found telemedicine implementation enhanced privacy, while others felt unable to ensure privacy in a virtual space. Participants found telemedicine modalities useful for counseling patients considering methods of LARC, but they sometimes presented an unnecessary extra step for those sure about receiving one at a practice offering same day insertion. Conclusion: Providers felt telemedicine provision of contraception positively impacted patient care. Improvements to counseling and easier access to method switching suggest that telemedicine implementation may help reduce contraceptive coercion. Our findings highlight the need to integrate LARC care with telemedicine workflows, improve patient privacy protections, and promote equitable access to all telemedicine modalities.